The Effect of Private School Vouchers on Political Participation: Experimental Evidence From New York City. Issue 3 (3rd July 2017) - Carlson, Deven; Chingos, Matthew M.; Campbell, David E.
ABSTRACT: In 1997, the New York School Choice Scholarships Foundation Program (SCSF) randomly offered three-year scholarships to attend private schools to approximately 1, 000 low-income families in New York City. In this paper we leverage exogenous variation generated by the SCSF to estimate the causal effect of the private school voucher offer—and the private school attendance it induced—on later-life voter registration and turnout outcomes. Our results demonstrate that the voucher intervention had no effect on registering to vote or voting in any of several elections for either the full sample or any of several demographic subgroups. Although unique aspects of the SCSF context impose limits on the scope of our results, they have clear implications for assessing the relative effectiveness of public and private schools in preparing democratic citizens. We close the paper by discussing the implications of the results for research and policy.